Experimental Study on the Effect of Large Temperature Difference on Compressive Strength and Pore Structure of Semirigid Base - Ming Dai; Jia Pan; Yanjun Shen; Jianbo Deng; Yeermulati Muhadeer (Advances in Civil Engineering)
Understanding the evolution of mechanical properties and pore structure of semirigid base under large temperature difference is of great significance for evaluating the durability and safety of semirigid base structure and studying the damage cracking mechanism and prevention technology of semirigid base induced by large temperature difference climate. This paper studies the variation law of peak stress and dynamic modulus, the evolution characteristics of pore structure, and the pore size distribution of semirigid base after different cycles at different temperature intervals. Based on the analysis of peak stress and dynamic modulus test results, the degradation effect of freeze-thaw environment (−20°C∼20°C) on semirigid base is far greater than that of high-temperature environment (20°C∼60°C) and low-temperature environment (−5°C∼−30°C). There are significant decreases in peak stress and dynamic modulus of semirigid base in the late cycle (12 to 15 cycles). Under low-temperature and freeze-thaw environments, the axial load resistance of semirigid base is significantly correlated with the deformation resistance, and the correlation between the two is not significant under high-temperature environment. The variability of the thermal expansion and contraction characteristics of the internal microscopic phases of the semirigid base and the force characteristics of the pore interface phases are the root causes of the damage and cracking of the pavement base in a large temperature difference climate.